Characterization of the radiation and matter transfer functions - Vija Suarez, Oscar Javier (Scientia et Technica, 2018)
This paper shows the characterization of the matter and radiation transfer functions. The transfer functions provide information about behavior of every species perturbation during radiation epoch, which allows to determine the evolution of these species during matter epoch. Graphics of the radiation and matter transfer functions, using the software CAMB are presented, in order to explain how large structures were formed.